(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
There is description of empirical research and results of the analysis of level of shyness from level of computer dependence in article. We have analysed main reasons for emergence of Internet dependence and its consequence – shyness. in conclusion, we have made decision that people with Internet dependence have difficulties in communication in real life.